The Rowperfect rowing simulator - Rekers, C.
Perfect coordination is the prime factor. For many people, the main attraction in rowing is the permanent quest for the optimum combination of force, endurance and perfect coordination. Experience shows that coordination is the most difficult to train of these three factors. It is, therefore, surprising that so many rowers should spend quite a lot of their precious time improving their strength and/or endurance using equipment which induces a coordination pattern between the main muscle groups that is absolutely detrimental to good rowing. It is the intention of this article to indicate how to improve this situation. The dynamic behaviour of a "fixed stretcher" ergometer differs quite considerably from that of a light racing shell floating freely on the water. Dynamically, such an ergometer reacts similarly to a boat that is infinitely heavy or solidly embedded in concrete, or as a rowing basin. Rowing on it, the rower moves his mass relative to the environment, back and forth, over the full length of the slide. On the water, however, this same rower, while moving over the full length of the slide relative to the boat, moves much less in relation to the environment (approximately only one fifth of the slide length). In this case, the relatively light racing shell moves a lot more than the much heavier rower (Lit 1). This big difference in dynamic behaviour makes any ergometer with a fixed stretcher a poor boat simulator.